Leaf expansion in grasses under salt stress - Taleisnik, Edith (2009)
Restriction of leaf growth is among the earliest visible effects of many stress conditions, including salinity. Because leaves determine radiation interception and are the main photosynthetic organs, salinity effects on leaf expansion and function are directly related to yield constraints under saline conditions. The expanding zone of leaf blades spans from the meristem to the region in which cells reach their final length. Kinematic methods are used to describe cell division and cell expansion activities. Analyses of this type have indicated that the reduction in leaf expansion by salinity may be exerted through effects on both cell division and expansion. In turn, the components of vacuole-driven cell expansion may be differentially affected by salinity, and examination of salinity effects on osmotic and mechanical constraints to cell expansion have gradually led to the identification of the gene products involved in such control. The study of how reactive oxygen species affect cell expansion is an emerging topic in the study of salinity's regulation of leaf growth.